Tricky Coyote tales - Schweizer, Chris; Thomas, Chad (Minneapolis : Graphic Universe, 2011)
Coyote seeks food and fun in the canyons and hills of the southwest, and the reader helps him make choices as he encounters many other creatures, some friendly and some dangerous.
Keywords: Plot-your-own stories; Coyote (Legendary character) -- Fiction; Tricksters -- Fiction; Animals -- Fiction; Plot-your-own stories; Coyote (Legendary character) -- Fiction; Animals -- Fiction; Plot-your-own stories; Graphic novels